Electronic system for experimentation in ac electrogravimetry I : technique fundamentals (2006)
RESUMEN: Basic fundamentals of AC electrogravimetry are introduced. Their main requirements and characteristics are detailed to establish the design of an electronic system that allows the appropriate extraction of data needed to determine the electrogravimetric transfer function (EGTF) and electrochemical impedance (EI), in an experimental set-up for the AC electrogravimetry technique.